Replacement name for Euwintonius insulanus Suzuki, 1982 (Opiliones: Laniatores: Assamiidae: Dampetrinae), primary junior homonym of E. insulanus Roewer, 1940 - Ponting, John (Zootaxa, 2015)
In 1940, Roewer described an assamid harvestman from New Guinea and named it Euwintonius insulanus Roewer, 1940. In 1982, Suzuki described a species in the same genus from the Bismarck Archipelago and gave it the same name. It is clear from the descriptions that these are two different species and Suzuki’s name is a primary junior homonym. Therefore, Euwintonius bismarckensis nomen novum is proposed here, as a replacement name for Euwintonius insulanus Suzuki, 1982. The specific epithet refers to the type locality of Suzuki’s specimen. There are four species in this genus, which can be separated by means of the following key.